IMPLEMENTASI METODE WEIGHTED PRODUCT UNTUK PEMILIHAN BIDAN TERBAIK PADA PUSKESMAS LALANG BATUBARA - Hutahaean, Jeperson; Eska, Juna (Riau Journal Of Computer Science, 2019)
This study aims to determine the best Midwife determination system in Puskesmas Lalang Batubara, designing and implementing Weighted Product method for the process of determining the best Midwife in Puskesmas Lalang Batubara in determining the best midwife by using decision support system using Weighted Product method. The research method used in this research is quantitative method. The result is the best Midwife selection decision support system at Puskesmas Lalang Batubara using Weighted Product method facilitate the Midewife in determining the best midewife best